НЕМИС ТИЛИ ДАРСЛАРИДА НУТҚНИ РИВОЖЛАНТИРИШДА ОНА ТИЛИНИНГ ТАЪСИРИ - Есбергенова, Г.Б. (SCIENCE and SOCIETY, 2020)
The article deals with different factors influencing on speech development of learners and also the role and place ofmother tongue in this process.
Keywords: mother tongue; speech; education; content; psychological and pedagogical training; method